(untitled) (Research, Society and Development, 2022)
There are few works in the literature regarding the study and development of new bioceramic compounds for ophthalmologic applications, especially considering the use of advanced laboratory technologies such as the sol-gel process, which presents the possibility of controlling various parameters as namely temperature, stoichiometry and alkalinity. In this regard, the present work synthesized alumina-based bioceramic compounds in combination with silica and zirconia via the sol-gel process, having evaluated the possibility/viability of these biomaterials for orbital reconstruction. The materials were characterized by X-Ray Diffraction (XRD), Fourier-Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscopy (SEM). The results show the formation of different structures, with the tendency to form alpha alumina, silica in the form of orthorhombic mullite and zirconia in its monoclinic and tetragonal phases, demonstrated by the characteristic reaction bonds between the precursors, as observed in the FTIR assay. The morphological characterization highlighted that the most determining factor which influences agglomerate size is temperature, followed by silica concentration. These results are relevant for ophthalmological applications, considering the intrinsic properties of each oxide.